SELF-ASSESSMENT AND PEER-ASSESSMENT FOR STUDENTS’ ESSAY ASSESSMENT IN THE AUFSATZ II COURSE - Tamara Carolin Fitrisia; Primardiana Hermilia Wijayati (Universitas Negeri Makassar, 2021)
Self-assessment and peer assessment is an essential alternative assessment in this 5.0 era and in this pandemic time. Thus, this study objectives are to examine differences between self-assessment and peer assessment, as well as to describe students' perceptions of the application of self-assessment and peer assessment in the Aufsatz II course. This study uses a correlational research design. From the results of the study, it is known that the self-assessment and peer assessment of Aufsatz's writing ability has some differences in the aspects of content and coherence, while self assessement and peer assessments for the aspects of vocabulary, orthography, and grammar have no significant differences. Students still find some difficulties in making self-assessment and peer assessments, and they prefer teacher assessments to self-assessment and peer assessments.